2023
DOI: 10.1186/s12906-023-03909-w
|View full text |Cite
|
Sign up to set email alerts
|

Protocol and biomarker strategy for a multi-site randomized controlled trial examining biological mechanisms and dosing of active music engagement in children with acute lymphoblastic leukemia and lymphoma and parents

Abstract: Background Music therapy is a standard palliative care service in many pediatric and adult hospitals; however, most research has focused on the use of music to improve psychosocial dimensions of health, without considering biological dimensions. This study builds on prior work examining psychosocial mechanisms of action underlying an Active Music Engagement (AME) intervention, designed to help manage emotional distress and improve positive health outcomes in young children with cancer and paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Additional research is needed to explore the benefits of AME over an early and longer course of treatment, and to ensure the intervention is culturally relevant and meaningful for all families. In our current trial, children are receiving the same chemotherapy regimen within a couple of months of diagnosis to increase the homogeneity of the timepoint and provide support earlier in the treatment trajectory 49 . Focus groups will explore perspectives of parents from underrepresented racial and ethnic backgrounds to ensure AME content and experiences are meaningful and relevant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional research is needed to explore the benefits of AME over an early and longer course of treatment, and to ensure the intervention is culturally relevant and meaningful for all families. In our current trial, children are receiving the same chemotherapy regimen within a couple of months of diagnosis to increase the homogeneity of the timepoint and provide support earlier in the treatment trajectory 49 . Focus groups will explore perspectives of parents from underrepresented racial and ethnic backgrounds to ensure AME content and experiences are meaningful and relevant.…”
Section: Discussionmentioning
confidence: 99%
“…In our current trial, children are receiving the same chemotherapy regimen within a couple of months of diagnosis to increase the homogeneity of the timepoint and provide support earlier in the treatment trajectory. 49 Focus groups will explore perspectives of parents from underrepresented racial and ethnic back-…”
Section: Counteracts Sufferingmentioning
confidence: 99%
“… Quantitative studies : In their RCT, Robb et al report improvement in health outcomes of courageous coping, social integration, and family environment during high-risk cancer treatment using therapeutic music video interventions [ 10 ]. Another RCT and a single case design pilot study from Robb et al point out the positive effects of active music interventions on multiple biomarkers to improve understanding of dose–response effects [ 20 , 21 ], as well as treatment fidelity in music-based play interventions for young children with cancer and their parents [ 22 ]. In addition, a pilot RCT by Robb et al investigated the feasibility and acceptability of parent-delivered active music engagement.…”
Section: Introductionmentioning
confidence: 99%
“…In the studies we evaluated and selected for this purpose, evidence was found that music-based interventions have positive effects on psychological well-being [ 17 , 24 ], competence, resilience, and interactive affect regulation [ 14 ]. Positive effects have been found in relation to cognitive and physiological aspects [ 12 ], as indicated by biomarkers in form of cortisol and immune function measurements [ 20 , 21 ] and measurement of heart rates, respiratory rates, and blood pressure [ 29 ]. Music therapy has also been claimed to support family functioning and social integration [ 10 , 16 , 18 , 19 , 30 ].…”
Section: Introductionmentioning
confidence: 99%